Flow Boiling Heat Transfer of Grooved Copper Foam with Open Gap - Donghui Zhang; Lili Sun; Jijin Mao; Qinhui Lei; Daifen Chen; Alexey P. Levtsev (Инженерные технологии и системы, 2022)
Introduction. Copper foam material has various advantages. It has been proved effective in enhanced boiling heat transfer, but also increases pump power consumption. Grooved copper foam is a solution to achieve good balance between boiling heat transfer characteristics and pump power consumption. Material and Methods. Grooveless and grooved copper foam in open space was studied. Copper foam specifications comprised the combination of porosities of 70, 80 and 90%, and pore densities of 90 and 110 PPI. The grooved copper foams have two specifications: 11 and 17 grooves. The corresponding rib widths are 2 and 1 mm, with groove depth 2.9 mm and width 0.6 mm. The flow boiling experimental system of copper foam sample includes four parts: a heating water reservoir, pump, a test section, and a data acquisition system. In the test section, liquid water turns into vapor and carries the heat away from a copper block surface, and then vapor condenses into liquid water in the terminal reservoir. Results. Grooved copper foam samples presented significantly higher efficiency than grooveless ones. Grooved copper foams can increase the critical heat flux and heat transfer coefficient, compared with grooveless ones. Seventeen-grooved samples showed more excellent performance than 11-grooved ones. Visual observation disclosed that the stratified flow pattern dominated in moderate and high heat flux for grooved copper foam with open space. Covering vapor mass was more effective to be formed above 17-grooved samples, compared with 11-grooved ones. It indicated more vigorous boiling behavior occurs in 17-grooved sample. Discussion and Conclusion. The number of grooves has a significant impact on boiling heat transfer. Grooved copper foam samples present a significantly higher critical heat flux and heat transfer coefficient. Structural parameters such as porosity and pore density, play a relatively secondly role in heat transfer argumentation. Visual observation shows there exists a cyclic alternation of flow patterns: bubbly flow, annular flow and mass vapor formation for grooved samples. Forming vapor mass is more effective to be formed in 17-grooved samples, compared to 11-grooved ones. It indicates more vigorous boiling behavior occurs in 17-grooved samples.